2016
DOI: 10.15441/ceem.15.069
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of blind intubation through supraglottic devices and direct laryngoscopy by novices: a simulation manikin study

Abstract: ObjectiveThis study aimed to compare intubation performance between blind intubation through supraglottic airway devices and direct laryngoscopy by novices under manikin simulation. We hypothesized that the intubation time by novices using supraglottic airway devices was superior to that with the Macintosh laryngoscope (MCL).MethodsA prospective, randomized crossover study was conducted with 95 participants, to evaluate i-gel, air-Q, LMA Fastrach, and MCL devices. Primary outcomes were the intubation time and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
(43 reference statements)
0
5
1
Order By: Relevance
“…Similarly, in a study by Kim et al the success of applying the tracheal tube in mannequin simulation in the AirQ-ILA method was lower than the LMAfastrach method. However, unlike in our study, the duration for applying the tracheal tube under mannequin simulation in the AirQ-ILA group was less than that of the LMAfastrach group ( 25 ).…”
Section: Discussioncontrasting
confidence: 88%
“…Similarly, in a study by Kim et al the success of applying the tracheal tube in mannequin simulation in the AirQ-ILA method was lower than the LMAfastrach method. However, unlike in our study, the duration for applying the tracheal tube under mannequin simulation in the AirQ-ILA group was less than that of the LMAfastrach group ( 25 ).…”
Section: Discussioncontrasting
confidence: 88%
“…5,6 ETI, which prevents airway obstruction and facilitates airway management, is preferred by hospitals, although performing it requires high skill. 7 Various SGAs such as the esophageal obturator airway, laryngeal mask, laryngeal tube, and I-gel device are being disseminated to assist healthcare providers to maintain open airways with minimal training. 8,9 With the increase in the proportion of level 1 emergency medical technicians (EMTs) among the 119 emergency medical service (EMS) agencies in South Korea, there has been an increasing trend toward performing advanced airway management, including ETI and SGA use, during the prehospital phase.…”
Section: Introductionmentioning
confidence: 99%
“…42 Other studies have used simulation to test the effectiveness of a GEB during chest compressions or to test the success rate of blind intubations through supraglottic devices. 43 44 Setting precedent for our work, the previously mentioned study by Melzer et al showed that innovative storage modalities can also be assessed in simulation. 32 Even more recent research highlights the value of simulation in studying intubation practices aimed at minimising airborne exposure to COVID-19.…”
Section: Discussionmentioning
confidence: 99%